Bonobo Cognition and Behaviour - Cahn, Claude (Brill, 2015)
This volume includes twelve novel empirical papers focusing on the behaviour and cognition of both captive and wild bonobos (''Pan paniscus''). Overall it demonstrates how anyone interested in understanding humans or chimpanzees must also know bonobos.